How U.S. children's hospitals define population health: a qualitative, interview-based study - Daniel Skinner; Berkeley Franz; Matthew Taylor; Chantelle Shaw; Kelly J. Kelleher (BMC, 2018)
Abstract Background The literature suggests that although adult hospitals are establishing population health programs around the country, there is considerable definitional ambiguity regarding whether interventions are aimed at the social determinants of health or the management of existing patient populations. U.S. children's hospitals also undertake population health programs, but less is known about how they define population health. The purpose of this study is to understand how U.S. children's hospitals define population health, and how institutions are adjusting to new preventive health care models. Methods We conducted semi-structured interviews with key stakeholders at ten hospitals with the highest amount of staff time dedicated to population health activities as reported in the 2016 Children's Hospital Association's population health survey. Using a semi-structured interview guide, we interviewed representatives from each hospital. Verbatim interview notes were coded and analyzed using the data analysis software Dedoose. Data analysis followed a modified constructivist grounded theory approach. Results Our results suggest that even population health innovators employ a variety of approaches that span both population health management and public health. We present further evidence that U.S. children's hospitals are actively debating the definition and focus of population health. Conclusions Definitional debates are ongoing even within children's hospitals that are dedicating significant resources to population health. Increased clarity on the conceptual boundaries between population health and population health management could help preserve the theoretical differences between the two concepts, especially insofar as they mark two quite different long-term visions for health care. Without agreement about the meaning of population health within and among institutions, hospitals will not be able to know whether projects aimed at addressing the social determinants of health are likely to improve the health of populations.